Emergence of Multidrug Resistant Enterococcus Species Isolated from Clinical Samples in North India (Global Journal of Medical Research, 2023)
Abstract not found
Keywords: high-level gentamicin resistance (HLGR); vancomycin resistant enterococci (VRE)